2009
DOI: 10.1021/la902623c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nanoscale Roughness of Titanium Thin Film Surfaces on Bacterial Retention

Abstract: Two human pathogenic bacteria, Staphylococcus aureus CIP 68.5 and Pseudomonas aeruginosa ATCC 9025, were adsorbed onto surfaces containing Ti thin films of varying thickness to determine the extent to which nanoscale surface roughness influences the extent of bacterial attachment. A magnetron sputter thin film system was used to deposit titanium films with thicknesses of 3, 12, and 150 nm on glass substrata with corresponding surface roughness parameters of R(q) 1.6, 1.2, and 0.7 nm (on a 4 microm x 4 microm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
154
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 187 publications
(163 citation statements)
references
References 43 publications
(79 reference statements)
8
154
1
Order By: Relevance
“…The 25 W polymer layer is smooth on the sub-nano-scale roughness level compared to unmodified substrate; therefore the current -attachment point‖ theory [46][47] that suggests that bacterial cells prefer microscopic surface irregularities as the starting point for their attachment as these provide shelter from unfavorable environmental influences clearly also cannot explain the attachment behavior. Our recent studies found that nano-scale surface roughness may have a notable effect on bacterial attachment and adhesion, with nano-scale fluctuations in roughness exerting a significant influence on the cellular response to certain surfaces [18,42,48]. The results presented here show that a higher number of bacterial cells were able to colonize the nano-smooth 25 W polymer coated substrates, whereas less smooth, unmodified glass substrates sustained a significantly lower level of cellular attachment.…”
Section: Discussionmentioning
confidence: 53%
“…The 25 W polymer layer is smooth on the sub-nano-scale roughness level compared to unmodified substrate; therefore the current -attachment point‖ theory [46][47] that suggests that bacterial cells prefer microscopic surface irregularities as the starting point for their attachment as these provide shelter from unfavorable environmental influences clearly also cannot explain the attachment behavior. Our recent studies found that nano-scale surface roughness may have a notable effect on bacterial attachment and adhesion, with nano-scale fluctuations in roughness exerting a significant influence on the cellular response to certain surfaces [18,42,48]. The results presented here show that a higher number of bacterial cells were able to colonize the nano-smooth 25 W polymer coated substrates, whereas less smooth, unmodified glass substrates sustained a significantly lower level of cellular attachment.…”
Section: Discussionmentioning
confidence: 53%
“…22,25 More importantly, this process appears to be independent of surface chemistry, meaning that bacteria are unable to develop a protective response. 1,2,[15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Such surface nanostructuring provides a viable replacement for conventional antibacterial surface technologies that involve the incorporation of antibiotics or additive chemicals. A comparative analysis of biocidal nanostructures has suggested that short, sharp nanofeatures tend to exhibit greater biocidal behavior;…”
Section: Introductionmentioning
confidence: 99%
“…1,20 For example, decreased adhesion of Staphylococcus aureus and Pseudomonas aeruginosa on Ti films has been reported when the nanoroughness was increased. 21 An effective approach to prevent BAIs would be to combine an antimicrobial release coating with a low bacterial adhesive material, for example, by introducing a specific nanoroughness. 22 One promising coating in this respect is mesoporous thin films, since they have roughness values in the nano regime combined with the ability to host and deliver antimicrobial drugs.…”
Section: Introductionmentioning
confidence: 99%